A template oriented one-dimensional Schiff-base polymer: towards flexible nitrogen-enriched carbonaceous electrodes with ultrahigh electrochemical capacity. Issue 45 (17th November 2021) - Xiao, Zhichang; Han, Junwei; He, Haiyong; Zhang, Xinghao; Xiao, Jing; Han, Daliang; Kong, Debin; Wang, Bin; Yang, Quan-Hong; Zhi, Linjie
Abstract : Schiff-base-type polymer is successfully integrated into one-dimensional structure. The derived nitrogen-doped porous carbon nanofibers are proved to be ideal energy storage electrode materials in supercapacitor and lithium-ion capacitor. Abstract : Lithium-ion capacitors (LICs) have attracted much attention considering their efficient combination of high energy density and high-power density. However, to meet the increasing requirements of energy storage devices and the flexible portable electronic equipment, it is still challenging to develop flexible LIC anodes with high specific capacity and excellent rate capability. Herein, we propose a delicate bottom-up strategy to integrate unique Schiff-base-type polymers into desirable one-dimensional (1D) polymeric structures. A secondary-polymerization-induced template-oriented synthesis approach realizes the 1D integration of Schiff-base porous organic polymers with appealing characteristics of a high nitrogen-doping level and developed pore channels, and a further thermalization yields flexible nitrogen-enriched carbon nanofibers with high specific capacity and fast ion transport. Remarkably, when used as the flexible anode in LICs, the NPCNF//AC LIC demonstrates a high energy density of 154 W h kg −1 at 500 W kg −1 and a high power density of 12.5 kW kg −1 at 104 W h kg −1 . This work may provide a new scenario for synthesizing 1D Schiff-base-type polymer derived nitrogen-enriched carbonaceous materials towards promising free-standing anodes in LICs.